Effect of Eye Exercises on Computer Vision Syndrome among Medical Students of Universitas Sumatera Utara, Indonesia - Zhuang, Angella; Sitepu, Bobby Ramses Erguna (International Journal of Integrated Health Sciences, 2023)
Objective: To determine the effect of eye exercises on Computer Vision Syndrome among batch 2019 medical students of the Faculty of Medicine, Universitas Sumatera Utara, and Indonesia.Methods: This study used analytical true experimental with a Pretest-Posttest Control Group Design. Sample consisted of 86 respondents who were divided into two groups: control and experimental (intervention) groups. Each group consisted of 43 respondents who were sampled randomly using the simple random sampling technique.  Data were collected through the Computer Vision Syndrome Questionnaire (CVS-Q) and analyzed using a statistical software application with a p-value of < 0.05 considered significant.Results: A decrease in the score of Computer Vision Syndrome in the experimental (intervention) group after the eye exercise was observed with a p-value of 0.001 (<0.05). Conclusion: Eye exercise has an effect on the Computer Vision Syndrome.